Enhancing Learning Independence Through Project-Based Learning: A Qualitative Study of Integrated Science Instruction in Indonesian Elementary Schools - Yuanita, Pita; Budiono, B.; Husamah, H.; Lambensa, Hawaree (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2026)
This descriptive study explored how Project-Based Learning (PjBL) was associated with indicators of learning independence among fifth-grade students in Integrated Science (IPAS) at Muhammadiyah 4 Batu Elementary School, Indonesia. Existing elementary PjBL research rarely examines behavioral indicators of learning independence or triangulates teacher, student, and observational data in IPAS contexts, creating a gap that this study seeks to address. A qualitative descriptive approach was employed, involving 87 students (three Grade 5 classes) and three teachers. Data were collected through interviews, questionnaires, classroom observations, and document analysis, then analyzed using the Miles and Huberman interactive model, complemented with descriptive proportions from 3-point Likert scales. High scores were defined as ratings ≥3 (“always/consistent”) on a three-level rubric; thresholds were established through expert validation. The percentages reported in this study represent the proportion of students categorized as “High” according to these validated thresholds. Inter-rater agreement for observations reached κ = 0.86, indicating substantial consistency. Findings reveal that PjBL was associated with higher observed levels of responsibility, confidence, initiative, and discipline through hands-on projects, collaborative discussions, and reflective presentations. Quantitative descriptive data showed that 83.9% of students demonstrated high responsibility, 87.4% high confidence, and 86.2% high discipline. Teacher interviews confirmed that PjBL enhances student engagement, though time management remains a challenge. The study concludes that PjBL-based instruction corresponded with behavioral indicators of learning independence and 21st-century competencies. However, as a single-site, descriptive investigation, no causal inferences can be drawn. Future research should apply validated independence scales and multi-site designs.